Globally elevated chemical weathering rates beneath glaciers - Li, Xiangying; Wang, Ninglian; Ding, Yongjian; Hawkings, Jon R.; Yde, Jacob C.; Raiswell, Robert; Liu, Jintao; Zhang, Shiqiang; Kang, Shichang; Wang, Rongjun; Liu, Qiao; Liu, Shiyin; et al. (Nature communications, 2022)
Physical erosion and chemical weathering rates beneath glaciers are expected to increase in a warming climate with enhanced melting but are poorly constrained. We present a global dataset of cations in meltwaters of 77 glaciers, including new data from 19 Asian glaciers. Our study shows that contemporary cation denudation rates (CDRs) beneath glaciers (2174 ± 977 Σ*meq + m − 2 year − 1 ) are ~3 times higher than two decades ago, up to 10 times higher than ice sheet catchments (~150-2000 Σ*meq + m − 2 year − 1 ), up to 50 times higher than whole ice sheet means (~30-45 Σ*meq + m − 2 year − 1 ) and ~4 times higher than major non-glacial riverine means (~500 Σ*meq + m −2 year − 1 ). Glacial CDRs are positively correlated with air temperature, suggesting glacial chemical weathering yields are likely to increase in future. Our findings highlight that chemical weathering beneath glaciers is more intense than many other terrestrial systems and may become increasingly important for regional biogeochemical cycles. Global glacial chemical denudation is one of the largest contributors to global elemental cycles and, amplified by climate warming, will significantly impact nutrient loads in downstream ecosystems.